Implementasi Pembelajaran Pendidikan Agama Islam Dalam Persfektif Kurikulum Tingkat Satuan Pendidikan - Husnul Mu'amalah (MKKS SMA, MKKS SMP se-Kota Metro, Persatuan Sarjana Pendidikan Islam Wilayah Provinsi Lampung, dan CV.IQRO Penerbitan, 2019)
The education unit level curriculum (KTSP) for PAI subjects needs to be evaluated and implemented properly by teachers so that academic quality can be improved. The findings of this study conclude: Implementation of KTSP in PAI subjects begins with: (1) Knowing the purpose of education. (2) Prepare syllabus and lesson plans (3). The PAI learning process which is implemented based on the KTSP is carried out by means of PAI teachers preparing syllabus, completing lesson plans, coordinating teachers once a month or incidental class visits by principals and supervisors. (4) The use of facilities and infrastructure by PAI teachers in implementing the KTSP has been relatively good. (5) Obstacle factors faced (a) Low motivation to learn about KTSP. (b) The competence of teachers who lack dedication. (c) Lack of cooperation from related parties. (d) Unfavorable environment. (e) There are still those who teach less prepared. Supporting factors: (a) teachers have high dedication. (b) The ability of teachers who always conduct evaluations. (c) Government policy.